2021
DOI: 10.1111/aepr.12362
|View full text |Cite
|
Sign up to set email alerts
|

Responses to COVID‐19 in Southeast Asia: Diverse Paths and Ongoing Challenges

Abstract: Due to geographical proximity and trade links with China, Southeast Asian countries were among the first to be exposed to and affected by COVID‐19. However, despite shared challenges including protecting population health and economic security, policy responses by national governments have been varied and remain so a year into the pandemic. This article critically reviews Southeast Asian countries' approaches to COVID‐19 with reference to individual country experiences and Association of Southeast Asian Nation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 7 publications
0
31
0
1
Order By: Relevance
“…This approach supports more precise prevention and mitigation of COVID-19, thus minimizing the cost of relevant resources. It was reported that Singapore and Vietnam provided medical equipment and support to neighboring countries [ 3 ], and we hope that there will be more multilateral collaborations among countries in SEA, especially considering the long-term challenges brought about by emerging new COVID-19 variants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This approach supports more precise prevention and mitigation of COVID-19, thus minimizing the cost of relevant resources. It was reported that Singapore and Vietnam provided medical equipment and support to neighboring countries [ 3 ], and we hope that there will be more multilateral collaborations among countries in SEA, especially considering the long-term challenges brought about by emerging new COVID-19 variants.…”
Section: Discussionmentioning
confidence: 99%
“…Countries in Southeast Asia (SEA) saw unprecedented challenges in health and social care systems, tourism, trade, and the service industry with the outbreak of COVID-19 [ 3 ]. Many countries in SEA made efforts to recover the economy during late 2020 and early 2021 by progressively easing lockdowns and strengthening export orders, but they were hammered by the wave of the new COVID-19 Delta variant [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…To ensure cooperation among countries in SEA, regional surveillance and information sharing should be indispensable for each country, which can support more precise control and prevention of COVID-19. Although some countries (Singapore, Vietnam) have made efforts to donate medical equipment and provide aid to their neighbors [3], we hope that there will be more interactive assistance among countries in SEA in the future, especially along the continuous emergence of COVID-19 variants. Furthermore, multilateral collaboration with countries or regions (e.g., European Union) outside SEA is considered as an effective and valuable way to help respond to the pandemic, although there will still be a long way to go in the future [3].…”
Section: Implications and Recommendationsmentioning
confidence: 99%
“…Health and social care system, as well as tourism, trade in essential goods and services of SEA countries were under pressure [3]. Hence, SEA countries with export-oriented economies like Cambodia, Vietnam, Singapore etc.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation